Ectoparasites Investigation on Non-Volant Small Mammals in Universiti Tun Hussein Onn Malaysia, Johor - Joshua, Juliana; Sapaat, Arney (Enhanced Knowledge in Sciences and Technology, 2026)
Non-volant small mammals, including rodents and tree shrews, serve as critical hosts for various ectoparasites and play significant ecological roles in urban and semi-natural ecosystems. This study surveyed ectoparasites on non-volant small mammals at Universiti Tun Hussein Onn Malaysia (UTHM), Parit Raja campus, and UTHM Tanjung Labuh, Johor. The study aims to identify the ectoparasite that infests non-volant small mammals, the distribution of ectoparasites on small mammals, and to understand the degree of specificity of each ectoparasite to the small mammal host. 30 live cages trapping method was employed across two main areas, including oil palm plantations, FPTP's lake, MyRivet, and UTHM Tanjung Labuh. The study focuses on identifying common ectoparasites such as ticks, lice, and mites, which pose potential zoonotic disease transmission risks to humans. Given the high degree of human-wildlife interaction in university campuses, understanding these host-ectoparasite dynamics is crucial for public health management and wildlife conservation. The finding will contribute to filling critical knowledge gaps regarding ectoparasite distribution patterns in highly urbanized environments and provide valuable insights for developing targeted intervention strategies to mitigate zoonotic disease risks. This study emphasizes the importance of monitoring ectoparasite populations in urban settings where human-wildlife interfaces are prominent, ultimately supporting both ecosystem health and public health initiatives in Malaysia's rapidly urbanizing landscapes.